ANALYSIS OF PHYSICAL PROPERTIES, PROPERTIES AND PROXIMATE CONDITIONS OF SNACK BAR FORMULATION OF RED RICE FLOUR (ORYZA NIVARA) AND GROUND NUTS (ARACHIS HYPOGAEA, L) - Damayanti, Santi; Inayah, Inayah; Nurjannah, Dewi (Jurnal Keperawatan Respati Yogyakarta, 2021)
Snack bar has a variety of nutrients and meets daily nutritional needs. Brown rice has high fiber levels, helps control blood sugar level. Objective of research to know the physical properties, level of preference, and proximate content of snack bars in various formulations of brown rice flour and peanuts. This type of research is Quasi experimental, using a completely randomized design (CRD) with 4 variations of brown rice flour A: 100%, B: 80%, C: 60%, and D: 50%.Result of research, Physical test of Snackbar was brown, flavored with brown rice flour, slightly sweet taste, and slightly soft texture. The most preferred Snackbar organoleptic test was snackbar D. The highest proximate, water content and carbohydrate test results were snackbar A, namely 25.57% and 58.83%. The highest ash content, fat content, protein content and fiber content of snackbar D were 2.2%, 15.49%, 11.63% and 1.00%. There are differences in color, there is no difference in smell, taste and texture of the four variations of the snackbar. The level of preference for color, smell, taste and texture is the highest at snackbar D. There are differences in water content, fat, crude fiber, protein and carbohydrates, there is no difference in ash content. Keywords: Snack bar; brown rice flour; peanuts